(3GdehLR aj bGfhf GdJLGQI GdOhdjIs - (3WGdH MSf(B, (3ehSis ((3YeGf(B;(3ecJHI OGQ GdKbGaI(B:s (3GdOGQ GdYdejI GdOhdjI(B,s, 2001)
(3GdJYQja HbGfhf GdJLGQI GdOhdjI, GJaGbjI GdCee GdeJMOI HTCf GdHjY GdOhdj ddHVGFY, GdJYQja HGdJMcje GdJLGQjs
Keywords: (3GdJLGQI GdOhdjIs; (3GdJMcje GdJLGQjs; (3bGfhf GdOhdj GdJLGQjs